About some problems of improving the activity of the body of inquiry - Violetta Urievna Gulakova (Вестник Северо-Кавказского федерального университета)
Examines the history and present state of the body of inquiry, as an institution of criminal procedure, suggests ways to improve the activity of the body of inquiry by reforming its structure and powers.